2022
DOI: 10.1007/s00167-021-06848-6
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in knee arthroplasty: specific data are key—a systematic review

Abstract: Purpose Artificial intelligence (AI) in healthcare is rapidly growing and offers novel options of data analysis. Machine learning (ML) represents a distinct application of AI, which is capable of generating predictions and has already been tested in different medical specialties with various approaches such as diagnostic applications, cost predictions or identification of risk factors. In orthopaedics, this technology has only recently been introduced and the literature on ML in knee arthroplasty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…This particular case is confirmed even by several recent reviews which proved evidence these types of features were not found in previous screenings. 23,24 Consequently, we will briefly discuss, in the following of this section, papers in the fields with a similar objective, still focusing on the predictive power of features for effective/potential classification studies. For instance, in 2020 Jafarzadeh and co-workers presented a preliminary study whose aim was to assess if both clinical and imaging features of OA could help to predict knee replacement over a 7-year period, including knees with and without radiographic OA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular case is confirmed even by several recent reviews which proved evidence these types of features were not found in previous screenings. 23,24 Consequently, we will briefly discuss, in the following of this section, papers in the fields with a similar objective, still focusing on the predictive power of features for effective/potential classification studies. For instance, in 2020 Jafarzadeh and co-workers presented a preliminary study whose aim was to assess if both clinical and imaging features of OA could help to predict knee replacement over a 7-year period, including knees with and without radiographic OA.…”
Section: Resultsmentioning
confidence: 99%
“…This particular case is confirmed even by several recent reviews which proved evidence these types of features were not found in previous screenings. 23 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…In a systematic review with grade III of evidence, Hinterwimmer et al analyzed ML algorithms for outcome prediction in TKA ( 17 ). The studies presented in such a review showed fair to good outcomes (AUC median 0.76/range 0.57–0.98), while heterogeneous prediction models were analyzed: complications ( 6 ), costs ( 4 ), functional result ( 3 ), revision ( 2 ), satisfaction after surgery ( 2 ), surgical procedure ( 1 ), and biomechanical properties ( 1 ) were studied.…”
Section: Virtual Elements Of Artificial Intelligence (Computer Scienc...mentioning
confidence: 99%
“… • Validation of wearable and ML-based surveillance platforms ( 15 ). • Prediction of distinct results with ML models applying specific data ( 17 ). Deep learning (DL) • Accurate identification of the presence of TKA and differentiation between specific arthroplasty designs ( 18 ).…”
Section: Virtual Elements Of Artificial Intelligence (Computer Scienc...mentioning
confidence: 99%
“…Machine learning represents a distinct application of AI, which describes algorithms for automatic and incremental function optimization. This can be used to make predictions by detecting non-linear relationships in large data sets [ 5 ]. Both offer tremendous new possibilities and clearly are promising options for the field of orthopaedic surgery, and in particular for total knee arthroplasty (TKA).…”
mentioning
confidence: 99%